HPB O02 Novel methods to modulate Nrf2 in liver regeneration. (7th December 2022) - Rehman, Adeeb; Copple, Ian; Diaz-Nieto, Rafael; Jones, Robert; Malik, Hassan; Fenwick, Stephen
Abstract: Background: The unique regenerative capacity of the liver permits curative surgery for patients with liver malignancy. However, extensive resections with a small future remnant liver risks post hepatectomy liver failure. Attempts to stimulate pre-resection liver regeneration have been refined over the last two decades. Techniques such as portal vein ligation/embolization, hepatic vein embolization and ALPPS are in clinical use. All these interventions aim to promote liver regeneration via a subtle anti-oxidative response in the contralateral lobe. The anti-oxidant transcription factor, nuclear erythoid 2-related factor 2 (Nrf2), has been strongly linked to enhancing liver regeneration. Furthermore, modulating Nrf2 pharmacologically has been shown to enhance liver regeneration, both structurally and functionally, in animal models of partial hepatectomy. Several Nrf2 activators (bardoxolone methyl (CDDO-Me), dimethyl fumarate, sulphoraphane) are in various phases of clinical trials, but each has potential unwanted off-target effects. One method to circumvent these effects would be to be use gene-specific therapy. Small activating RNA (saRNA), is a novel therapy using small RNA molecules to upregulate a specific gene. Here we present identification of a lead saRNA candidate to upregulate Nrf2. Methods: We obtained several human and mouse specific saRNAs, with different sequences, all designed to target Nrf2. Human specific saRNA was screened using a hepatoma cell line (HepG2) stably transfected with the firefly gene. A luciferase assay was used to determine Nrf2 expression. CDDO-Me was used as a positive control, and transfection excluding saRNA (mock transfection) used as a negative control. To ensure specificity of the lead candidates, further mutated versions were designed and tested using a similar method. Endogenous gene expression was measured using quantitative PCR.Identification of a lead mouse specific candidate was completed with a view to in vivo testing. Murine colorectal cancer (CT26) cells were transfected with the mouse specific saRNA. Mutated samples for ideal candidates were designed and tested in a similar fashion. Gene expression was performed by qPCR. Similar controls were used. Continuous data was assessed for normality using a Shapiro-Wilks test, and analysed with ANOVA (analysis of variance) with a Tukey multiple comparisons test for normally distributed data. Skewed data was analysed with a Kruskal-Wallis' test. A p value of <0.05 was considered significant. Results: Initial screening of 11 unique human specific saRNAs yielded 2 lead candidates, PR91b and PR145, with a 1.8 and 2.4 fold (p<0.0001) increase in Nrf2 expression compared to the mock transfection. Specificity was tested using mutated versions of the two lead candidates which revealed a specificity with primers Nrf2, NQO1, GCLC and GCLM (downstream Nrf2 targets) via qPCR. PR91b and PR145 upregulated a 1.5- and 1.4-fold increase in NQO1, a 1.8- and 1.9-fold increase in GCLC and a 2.2- and 2.0-fold increase in GCLM, respectively. The mutated versions showed minimal to no upregulation of Nrf2 or its downstream targets (p<0.001). Time course and dose response studies to optimise the transfection protocol demonstrated an optimal final saRNA concentration of 10nM over a transfection period of 4 days. Initial screening with qPCR of 11 unique mouse specific saRNAs yielded 1 lead candidate, PR60, with a 3.0- and 2.5-fold increase in genes Nrf2 and NQO1 respectively. Specificity was assessed with mutated saRNAs which showed minimal to no upregulation of the genes Nrf2 or NQO1. Conclusions: To date, there is only one Nrf2 activator licensed for use by the Medicines and Healthcare products Regulatory Agency – dimethyl fumarate for relapsing-remitting multiple sclerosis. Ongoing clinical trials exist aiming to utilise Nrf2 activators in liver related diseases as well as other non-hepatic diseases (such as treatment of diabetic nephropathy and COPD, amongst others). However, the inherent problem with such drugs are off-target effects. In this study we demonstrate upregulation of Nrf2 and its downstream targets by a novel and specific therapy – gene activation. Whilst not upregulating Nrf2 to the same degree as CDDO-Me in vitro, saRNA has the benefit of improved specificity, thereby eliminating off target effects.